An inquiry into the original of our ideas of beauty and virtue - Hutcheson, Francis; Leidhold, Wolfgang; Haaknossen, Knud (Indianapolis Liberty fund, 2004)
This work contains two treatises: concerning beauty, order, harmony, design, and concerning moral good and evil. There is no part of philosophy of more importance than a just knowledge of human nature and its various powers and dispositions. The author presents these papers as an inquiry into the various pleasures which human nature is capable of receiving. Written in Old English.